Handbook of service user involvement in nursing and healthcare research - Morrow, Elizabeth, 1975-; Boaz, Annette; Brearley, Sally; Ross, Fiona, 1951- (Chichester, West Sussex, UK : Wiley/Blackwell, 2012)
"This book fills an important niche in the market providing practical expert advice on the involvement of service users--patients, carers and the public--in nursing and healthcare research. An invaluable guide for anyone working or involved in nursing and healthcare research, this book provides a step-by-step guide to the principles and process of involvement, including understanding the rationale for involvement, designing involvement, working with service users, and evaluating what has been achieved. With illustrations, worked examples and tool sheets throughout, this evidence-based guide uses real life examples from recent research studies in health and social care research, thus relating theory to practice in a meaningful way. The Handbook of Service User Involvement in Nursing & Healthcare Research introduces a wide range of key issues, including: Why? Why should researchers involve service users?; How? How can researchers and service users work together successfully and productively?; Who? Who chooses to become involved in research? How are issues of representation and diversity addressed?; When? At what stage should service users be involved in the research process?"--Publisher's description.
Part I. Preparing -- Perspectives and Expectations -- Concepts -- Designing Involvement -- Working Relationships -- Part II. Learning -- Patients, Clients and Carers -- Involvement over the Life Course -- Seldom-Heard Groups -- Service User-Led Research -- Part III. Evaluating -- Quality -- Impact -- International Perspectives -- Conclusion.
Includes bibliographical references and index.
Print version record and online resource; title from PDF title page (EBSCOhost eBook Collection, viewed April 7, 2014).
Keywords: Nursing -- Research; Medical care -- Research; Medical personnel and patient; Nursing Research; Health Services Research; Patient Participation; Professional-Patient Relations; MEDICAL -- Nursing -- Research & Theory; Medical care -- Research; Medical personnel and patient; Nursing -- Research; Electronic books